Pengaruh Fungsi Manajemen Terhadap Kinerja Karyawan pada Pengelolaan Ikan Hias di PT Indotama Putra Wahana Bekasi, Jawa Barat - Mitra Sari Bulan; Mauli Kasmi; Mariam Mariam (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Every business has goals to achieve. To make it real efective and efficient company goals, it is important to improve employee performance. The aplication of managemen functions is an important factor in this matter. The purpose of this study is to determine the influence of each management function on employee performance in ornamental fish management at PT Indotama Putra Wahana, an ornamental fish export and import company. The research methods used are multiple linear regression analysis through research instrument tests (validity and reliability tests), classical assumption tests (normality tests and heteroscedasticity tests) and hypothesis tests using t tests, as well as correlation tests and determination coefficient tests. Through the t test on the planning function, tcount was obtained worth 4.643 > ttable worth 2.467 with a significance value of 0.000 < 0.05, which means that the planning function has a significant effect on employee performance. While in the organizing function, a tcount of 3.735 > ttable worth 2.467 was obtained with a significance value of 0.001 < 0.05, which means that the organizing function has a significant effect on employee performance. Then in the briefing function, a tcount of 3.737 > ttable worth 2.467 was obtained with a significance value of 0.001 < 0.05 which means that there is a significant influence on employee performance. In the control function, a calculation of 4.710 > ttable worth 2.467 was obtained with a significance value of 0.000 < 0.05, which means that the control function has a significant effect on employee performance. Then through the correlation test, a strong relationship was obtained between the management function and employee performance by 69.5%.